2021
DOI: 10.1002/ep.13639
|View full text |Cite
|
Sign up to set email alerts
|

Statistical optimization of photocatalytic degradation process of methylene blue dye by SnOTiO2AC composite using response surface methodology

Abstract: Photocatalytic activity of bi-metal oxides SnO-TiO 2 -AC photocatalyst was evaluated in methylene blue (MB) dye degradation In this study, a three-level, four-factor, D-optimal experimental design, combined with response surface methodology, was employed to optimize the photocatalytic degradation process of MB dye in a batch reactor. Effectiveness of essential process variables: light intensity (254-400 nm), initial dye concentration (100-200 ppm), photocatalyst dose (0.5-1.5 g/L), and irradiation time (1-5 h)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 38 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…To explore the crystal structural variations of TiO 2 and different cocatalyst-loaded TiO 2 samples, XRD and Raman characterizations were conducted, as shown in Figures S1 and S2. Bare TiO 2 , Cu 1.8 -TiO 2 (denoted as SNC-Cu/TiO 2 ), and Pt 1 -TiO 2 exhibited a typical anatase TiO 2 (JCPDS 04-013-5313, space group I 41/ amd ) pattern, and no impurity peaks were detected in Figure S1a, with three prominent diffraction peaks at 25.3°, 37.8°, and 48.0° observed, which can be indexed to (101), (004), and (200) crystal planes of anatase TiO 2 . Meanwhile, no apparent metallic diffraction peaks of Cu or Pt were observed in Cu 1.8 -TiO 2 and Pt 1 -TiO 2 , which may be attributed to the low loading amount and the noncrystalline structure of the ultrafine Cu clusters and Pt nanoparticles (NPs).…”
Section: Resultsmentioning
confidence: 99%
“…To explore the crystal structural variations of TiO 2 and different cocatalyst-loaded TiO 2 samples, XRD and Raman characterizations were conducted, as shown in Figures S1 and S2. Bare TiO 2 , Cu 1.8 -TiO 2 (denoted as SNC-Cu/TiO 2 ), and Pt 1 -TiO 2 exhibited a typical anatase TiO 2 (JCPDS 04-013-5313, space group I 41/ amd ) pattern, and no impurity peaks were detected in Figure S1a, with three prominent diffraction peaks at 25.3°, 37.8°, and 48.0° observed, which can be indexed to (101), (004), and (200) crystal planes of anatase TiO 2 . Meanwhile, no apparent metallic diffraction peaks of Cu or Pt were observed in Cu 1.8 -TiO 2 and Pt 1 -TiO 2 , which may be attributed to the low loading amount and the noncrystalline structure of the ultrafine Cu clusters and Pt nanoparticles (NPs).…”
Section: Resultsmentioning
confidence: 99%
“…However, the value of the interaction coefficients of the individual terms A, B, and C was found to be rather higher in comparison to the interaction term of factor AB. This further indicated that the optimization of this reaction is heavily dependent on the individual factors rather than on the interaction terms [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The photocatalytic decomposition of MO with c 0 = 130 µM under UV irradiation on the TS_Ag nanocomposites leads to a rate constant value of 43.95 × 10 −3 min −1 , while the equivalent rate recorded under Vis irradiation was lower, at 18.52 × 10 −3 min −1 (Table 1). There are many reports in the literature where the researchers combine the synergetic effects of TiO 2 and SnO 2 in order to increase their photodegradation performance on toxic contaminants in aqueous media [12,18,45,46]. Moreover, the metal nanoparticle's presence on the semiconductor matrix provides a better tunability for visible absorption [46], stops the recombination of e − /h + pairs, and enhances e − /h + separation, leading to an improvement in the photocatalytic performance.…”
Section: Photocatalyst-cleaning Up Hazardous Substancesmentioning
confidence: 99%